Pot- and atom-economic synthesis of oligomeric non-fullerene acceptors via C–H direct arylation. Issue 16 (4th April 2022) - Wang, Li-Hong; Chen, Xian-Jie; Ye, Dong-Nai; Liu, Hui; Chen, Yan; Zhong, Ai-Guo; Li, Chang-Zhi; Liu, Shi-Yong
Abstract : Three long-chain oligomeric acceptors with a stepwise increase in conjugation length are obtained via three successive one-pot reactions and a systematic structure–property–performance relationship study was carried out. Abstract : Despite the substantial increase in the power conversion efficiencies (PCEs) of organic solar cells (OSCs), access to organic photoactive materials still remains cumbersome and, hence, relatively high cost in terms of synthesis and purification. In this work, we report, for the first time, the pot- and atom-economic synthesis of oligomerized unfused non-fullerene acceptors (NFAs) via C–H direct arylation (DACH) with gradually increasing chain lengths, i.e., IDB-IC- n and IDBF-IC- n ( n = 1–3). These oligomeric NFAs have varied conjugation lengths but the same backbones of alternating indacenodithiophene and benzothiadiazole or difluorobenzothiadiazole. Note that IDB-IC-3 and IDBF-IC-3 have the longest conjugation lengths ever reported among oligomeric NFAs. Systematic studies of structure–property–performance relationships revealed that IDBF-IC-1 achieves the best PCE of 12.12%, accompanied by a decrease in the PCE with an increase in the oligomeric chain length. Our results demonstrate that the opto-electronic properties can be fine-tuned via varying the conjugation length or introducing fluoridated building units. Meanwhile, the highly efficient DACH reaction combined with the pot-economic strategy developed here could be a promising candidate for the synthesis of conjugated oligomers for future OSC applications.